Influence of copper addition on corrosion properties and hardness of Al–Cu/Al two-layered-structure composites. (March 2022) - Rajasekhar, Kotikala; Babu, V Suresh; Davidson, MJ; Raghavendra, G
An experimental investigation has been observed on hardness, sintered density and corrosion behaviour of two-layered structured Al-xCu/Al sample through powder metallurgical route under hot compaction condition. The samples were prepared with different percentages of Cu content (x: 5 wt. %, 10 wt. % and 15 wt. %) in the aluminium matrix with a constant pressure of 400 MPa with different hot-pressed temperatures (500 °C, 550 °C and 600 °C) at a dwelling time of 3 h. The developed two-layered samples microstructure was analysed using the optical and scanning electron microscope. The highest value of micro-hardness (100.6 HV) was obtained at interface region of 15% of copper at 550 °C. The corrosion rate of Al-Cu/Al two-layered samples at the interface were analyzed through the potentiodynamic polarization test and found that with addition of copper content the susceptibility of corrosion increases. The Electrochemical Impedance Spectroscopy (EIS) test was conducted to know the equivalent circuit model, which provides a minimum chi-square value and that circuit model taken as best-fit circuit model. From the EIS results, it was found that 10 wt. %Cu sample circuit provides minimum chi-square value.